Defect-rich ordered mesoporous carbon supported metal nanoparticle catalyst as well as preparation and application thereof
By building an orderly medium carbon load, inherent defects and loading metal nanoparticles, preparing the orderly and orderly order of the disadvantage of the carbon load metal nanoparticles catalyst, the DMFC anode catalyst material activation level poisoning and the slow response dynamic problem, realized efficiency Methanol electrocatalytic oxidation reactions and catalyst stability.
Patent Information
- Application Number
- CN202411451093.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
Existing direct methanol fuel cell (DMFC) anode catalyst materials have problems of active site poisoning and slow reaction kinetics, resulting in catalyst deactivation and low energy conversion efficiency.
By constructing the inherent defects of the ordered mesoporous carbon carrier, a defect-rich ordered mesoporous carbon material is prepared and loaded with metal nanoparticles to form a defect-rich ordered mesoporous carbon supported metal nanoparticle catalyst, which enhances its performance in the electrocatalytic oxidation reaction of methanol. overall performance.
A significant improvement of methanol electrocatalytic oxidation reaction dynamics and conductive capabilities, enhancing the interaction of metal-carrier, reducing the electronic cloud density of metal nanoparticles, and improving the stability and quality of catalysts.
Smart Images

Figure CN119340403A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst and the preparation and application thereof. Background Art
[0002] In order to achieve clean utilization of fossil energy, researchers have developed a series of energy conversion devices, such as fuel cells, lithium batteries, supercapacitors, etc. Among them, direct methanol fuel cells have the advantages of high energy density and energy conversion efficiency, no need to charge, and fast start-up at low temperatures, and are highly favored.
[0003] Direct methanol fuel cell (DMFC) is an energy conversion device that can directly convert the chemical energy stored in methanol into electrical energy. It is a type of proton exchange membrane fuel cell (PEMFC). DMFC has the following advantages: (1) High energy efficiency. The theoretical energy density of DMFC is about 6000W·h·kg -1 The theoretical energy conversion efficiency is as high as 96.68%, which is better than nickel-chromium batteries (40W·h·kg -1 ), NiMH battery (100W·h·kg -1 ), and lithium-ion batteries (600W·h·kg -1 ); (2) Low cost, methanol fuel is abundant and low in price (about 2,400 yuan / ton), the price of industrial-grade methanol is about 1 / 3 of gasoline and diesel, and the operating cost is only half of that of an internal combustion engine; (3) No pollution, no NOx, SOx and particulate matter emissions during operation, carbon emissions over the entire life cycle can be reduced by 40%, and zero carbon emissions can be achieved using renewable methanol. In addition, using methanol with a simple structure as fuel does not cause the problem of CC bond breaking, the reaction step barrier is low, and the electrochemical activity is high. Compared with hydrogen fuel cells, it has the advantages of abundant reserves, easy transportation and storage. Therefore, as a promising energy conversion device, DMFC has broad application prospects in distributed power generation, mobile power, communications, transportation and other fields.
[0004] Although DMFC has many advantages, the following challenges have not been well addressed: (1) Since platinum (Pt)-based catalysts are currently the most commonly used electrocatalysts for MOR, a series of carbonaceous intermediates (such as CO) generated during the MOR process often undergo strong chemical adsorption with the Pt surface, resulting in active site poisoning and severe catalyst deactivation; (2) The methanol oxidation reaction (MOR) at the DMFC anode has slow kinetics, which seriously reduces its energy conversion efficiency. To address the above challenges, researchers usually take the following two perspectives as entry points: First, by regulating the morphology, particle size, crystal surface composition of the active site and constructing alloy catalysts, the electronic structure of the active site is adjusted, the adsorption energy barrier of the carbonaceous intermediates is increased, and the catalyst deactivation phenomenon is effectively reduced; second, the selection of a suitable catalyst carrier or modification of the carrier can not only enhance the metal-carrier interaction, but also promote the mass transfer behavior of methanol molecules on its surface and improve the reaction kinetics. DMFC anode catalyst materials mainly include carbon materials and non-carbon materials (metal oxides, sulfides, carbides, etc.). Non-carbon materials have poor electrical conductivity and are prone to electrochemical corrosion at high potentials. Compared with non-carbon materials, carbon materials have the advantages of abundant resources and simple preparation, and have large specific surface area, developed pore structure, and acid and alkali resistance. Therefore, carbon materials are key anode catalyst carriers with great potential to promote the industrialization of direct methanol fuel cells. Ordered mesoporous carbon, as a type of carbon material, has a large specific surface area and uniform pore structure, which is conducive to the mass transfer and adsorption behavior of methanol molecules and metal nanoparticles on the catalyst surface. Therefore, ordered mesoporous carbon is a very promising anode catalyst carrier material for direct methanol fuel cells. However, pure ordered mesoporous carbon has few surface defects, and the anchoring of metal nanoparticles and the regulation of electronic structure are limited, which often leads to low mass specific activity. In addition, due to its amorphous nature, it often has poor stability.
[0005] Recently, some studies have proposed that the intrinsic defects of carbon carriers can improve the electrocatalytic activity by enhancing the adsorption of metal nanoparticles, adjusting the electronic structure of metal nanoparticles, and improving the conductivity. ([J.] Adv. Mater. Weinheim 28, 9532–9538.) The intrinsic defects of carbon carriers are divided into edge defects and topological defects. Topological defects in carbon skeletons usually exist in non-hexagonal structures such as pentagons, heptagons and octagons ([J.] Chem, 2018, 4, 2345-2356). In the process of preparing nitrogen-doped carbon, a calcination step is inevitably involved. During this process, the shedding of nitrogen species causes the reconstruction of carbon atoms and then leads to the generation of topological defects, which has a positive effect on the electrocatalytic activity ([J]. Angew. Chem., Int. Ed. 2019, 58, 3859). This is because when topological defects are introduced, the electronic symmetry of the aromatic ring is destroyed. This will cause local charge rearrangement, making the adjacent carbon atoms have stronger electron transfer ability. Yao et al. ([J]. Chem, 2018, 4, 2345-2356) constructed nitrogen-doped carbon nanofibers with different nitrogen configurations by regulating the degree of edge defects of carbon nanofibers. Then, the nitrogen species were removed at high temperature. The study found that the intrinsic defects produced after the removal of different nitrogen configurations were different: the adjacent pentagonal defects produced after the removal of pyrrolic nitrogen had the best reaction activity for the oxygen reduction reaction; while the divacancy defects produced after the removal of graphitic nitrogen were the main active sites for the hydrogen absorption reaction. Most importantly, the reaction activity after nitrogen removal was higher than that after nitrogen doping, which further illustrates that the defect sites produced after the nitrogen species fell off are the main contributors to the activity improvement. In addition, they also found ([J.] J. Am. Chem. Soc. 2022, 144, 5, 2171–2178) that the defective graphene prepared by the nitrogen removal strategy can anchor platinum single atoms to form a unique Pt-C3 configuration. Similar strategies for generating topological defects and thus improving catalytic activity have been widely studied in oxygen reduction, oxygen evolution reaction, and hydrogen evolution reaction. Common edge defects mainly exist in zigzag or armchair shapes. Ball milling usually introduces edge defects on the original carbon support, which will fill the carbon edge with a large number of unpaired π electrons and enhance the metal-support interaction. In metal-free catalysts, edge defects accelerate the transfer of electrons and reduce the adsorption energy of reaction intermediates. Wang et al. ([J]. International journal of hydrogen energy, 2021, 46, 30455-30466) used ball milling to prepare self-doped defect mesoporous carbon and used functional density theory calculations to predict that palladium nanoparticles on self-doped defect mesoporous carbon have stronger metal-support interaction (MSI) than original mesoporous carbon. This makes palladium (Pd) nanoparticles easily anchored by self-doped defect mesoporous carbon and optimizes the electronic structure of the catalyst.The prepared self-doped defective mesoporous carbon-supported palladium nanoparticle catalyst showed higher activity and stability than the original mesoporous carbon-supported palladium nanoparticles in ethanol oxidation and ethylene glycol oxidation. However, the defect type of defective carbon carriers prepared by ball milling is uncontrollable and has poor reproducibility. He et al. ([J.] Angewandte Chemie International Edition, 2024, 202403023.) used a soft template method to prepare palladium nanoparticle catalysts supported on mesoporous carbon spheres. Studies have shown that the advantage of introducing mesoporous structures lies mainly in their abundant edge defects, which not only provide sufficient sites for the nucleation and anchoring of palladium nanoparticles, but also enhance the electronic metal-support interaction between palladium nanoparticles and carriers, thereby reducing the electron cloud density of palladium nanoparticles, optimizing the adsorption of OOH* at the carbon edge, and ensuring a highly active two-electron oxygen reduction reaction process. In addition, strategies such as plasma technology ([J.] Adv. Mater. 29, 1606-207.) and potassium hydroxide etching ([J.] Angew. Chem. Int. Ed. 58, 3859-3864.) have been used to construct intrinsic defects in carbon supports. In summary, clarifying the effect of intrinsic defects in carbon supports on electrocatalytic reactions is crucial for the preparation of high-performance electrocatalysts. Summary of the invention
[0006] The purpose of the present invention is to provide a defect-rich ordered mesoporous carbon-loaded metal nanoparticle catalyst and its preparation and application. By constructing the inherent defects of the ordered mesoporous carbon carrier, a defect-rich ordered mesoporous carbon material is obtained, and then metal nanoparticles are loaded to form a defect-rich ordered mesoporous carbon-loaded metal nanoparticle catalyst, thereby enhancing its overall performance in the methanol electrocatalytic oxidation reaction.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst, comprising:
[0009] (1) dissolving 1 to 3 parts of a carbon source and 0.2 to 1.5 parts of a defect-causing agent in an appropriate amount of deionized water by weight to obtain a precursor solution; then adding 0.05 to 0.15 parts of concentrated sulfuric acid for dehydration, and then dispersing the mixed solution into 1 part of a hard template by ultrasonication, and then drying by gradient heating to obtain an ordered mesoporous carbon material intermediate;
[0010] (2) taking one portion of the ordered mesoporous carbon material intermediate, subjecting it to high temperature heat treatment in an inert atmosphere, then removing the hard template with a strong alkaline solution, then washing the product with water until it is neutral, and drying it, to obtain a solid product, which is defect-rich ordered mesoporous carbon;
[0011] (3) The ordered mesoporous carbon material obtained in step (2) is subjected to impregnation and chemical reduction steps with a metal precursor solution to obtain a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst.
[0012] Furthermore, in step (1), the carbon source is organic sugar.
[0013] Preferably, the carbon source is sucrose.
[0014] Furthermore, in step (1), the defect-causing agent is at least one of zinc chloride, zinc oxide quantum dots, potassium hydroxide, urea, and melamine.
[0015] Furthermore, in step (1), the hard template is a silica zeolite molecular sieve.
[0016] Preferably, the hard template is SBA-15.
[0017] Furthermore, in step (1), the dehydrated precursor solution is added to the hard template twice, and each time the drying is performed by gradient heating.
[0018] Preferably, the gradient temperature drying is carried out in a muffle furnace, firstly heating to 100°C at a heating rate of 1-3°C / min, maintaining for 6 hours, then heating to 160°C at a heating rate of 10-20°C / min, and maintaining for another 6 hours.
[0019] Furthermore, in step (2), the high temperature heat treatment under inert atmosphere is carried out in two stages, firstly, the temperature is increased to 600°C for pre-carbonization for 3 hours at a heating rate of 1 to 3°C / min, and then the temperature is increased to 1000 to 1200°C for carbonization for 2 hours at a heating rate of 5 to 10°C / min.
[0020] Furthermore, in step (2), the specific process of removing the hard template with a strong alkaline solution is as follows: the solid product after high-temperature heat treatment under an inert atmosphere is added to a strong alkaline solution, stirred for 24 hours in an oil bath at 60 to 100° C., and the operation is repeated three times.
[0021] Preferably, the strong alkaline solution is an aqueous solution of sodium hydroxide or potassium hydroxide with a mass percentage of 8-12%.
[0022] Furthermore, in step (3), the metal precursor used in the metal precursor solution is a metal precursor containing any one of Pt, Pd, Ru, Rh, Ir, Fe, Co, Ni, Cu, and Zn.
[0023] In a second aspect, the present invention provides a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst, which is prepared by the above-mentioned preparation method of the defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst.
[0024] Furthermore, the defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst has a pore size of 2 to 10 nm and a mass specific activity of 4000 to 5027 mA·mg -1 metal .
[0025] In a third aspect, the present invention proposes the use of the above-mentioned defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst in the electrocatalytic oxidation reaction of methanol at the anode of a direct methanol fuel cell.
[0026] Compared with the prior art, the technical advantages and progress of the present invention are:
[0027] (1) In the preparation method of a defect-rich ordered mesoporous carbon supported metal nanoparticle catalyst provided by the present invention, sucrose is used as a carbon source, and ordered mesoporous carbon with different intrinsic defect types and concentrations is obtained by using defect-causing agents of different types and amounts and different high-temperature carbonization temperatures; the intrinsic defect type can be regulated by changing the type of defect-causing agent, and the intrinsic defect concentration is regulated by changing the calcination temperature and the amount of defect-causing agent; the addition of the defect-causing agent significantly increases the intrinsic defect concentration of the ordered mesoporous carbon, promotes the adsorption of methanol and carbonaceous intermediates on the catalyst surface, improves the electronic structure of metal nanoparticles and the electron transfer kinetics, and the rich mesoporous structure promotes the mass transfer behavior of methanol molecules and enhances the catalyst surface reaction kinetics. Therefore, the defect-rich ordered mesoporous carbon prepared by the present invention not only effectively improves the kinetics and conductivity of methanol electrocatalytic oxidation reaction, but also the rich inherent defects enhance the metal-support interaction, effectively reduce the electron cloud density of metal nanoparticles, and promote the adsorption conversion of reaction intermediates. In addition, the anchoring effect on metal nanoparticles is also enhanced, effectively improving the stability of the electrocatalyst.
[0028] (2) The defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst prepared by the method of the present invention has a pore size of 2 to 10 nm and a mass specific activity of up to 5027 mA·mg -1 metal ; After 200s of constant potential discharge at -0.2V, the mass specific activity still reached 700mA·mg -1 metal .
[0029] (3) The method of the present invention has a simple overall process flow and high safety, and as a DMFC anode catalyst material, it exhibits excellent mass specific activity and stability, and has good application prospects and value in the field of methanol energy conversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1are scanning electron microscope (SEM) images of the catalysts prepared in Example 1 and Comparative Example 1, wherein a and b are scanning electron microscope images of the catalyst prepared in Comparative Example 1, and c and d are scanning electron microscope images of the catalyst prepared in Example 1 when the addition amount of ZnCl2 is 0.55 g;
[0031] Figure 2 The X-ray diffraction (XRD) patterns of the defect-rich ordered mesoporous carbon-supported palladium nanoparticle catalysts prepared in Example 1 and Comparative Example 1;
[0032] Figure 3 are nitrogen adsorption-desorption isotherms of the catalysts prepared in Example 1 and Comparative Example 1, wherein a is a nitrogen adsorption-desorption isotherm of the catalyst prepared in Example 1, and b is a nitrogen adsorption-desorption isotherm of the catalyst prepared in Comparative Example 1;
[0033] Figure 4 are Raman spectra of the catalysts prepared in Example 1 and Comparative Example 1, wherein a is the Raman spectra of the catalyst prepared in Comparative Example 1, and bd are the Raman spectra of the catalyst prepared in Example 1;
[0034] Figure 5 The chronoamperometric curves of the catalysts prepared in Example 1 and Comparative Example 1 in the electrocatalytic oxidation reaction of methanol;
[0035] Figure 6 The cyclic voltammetry curves of the catalysts prepared in Example 1 and Comparative Example 1 in the electrocatalytic oxidation reaction of methanol;
[0036] Figure 7 X-ray photoelectron spectra of the catalysts prepared in Example 1 and Comparative Example 1;
[0037] Figure 8 X-ray photoelectron spectra of the catalysts prepared in Example 2 and Comparative Example 2;
[0038] Fig. 9 The cyclic voltammetry curves of the catalysts prepared in Example 2 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings, but the implementation mode of the present invention is not limited thereto.
[0040] Example 1
[0041] Weigh 1.25g of sucrose and different masses of zinc chloride (0.275g, 0.55g, 1.1g) and place them in a centrifuge tube, then accurately measure 10.0mL of deionized water and add it to the above centrifuge tube, stir to form a uniform solution; then add 0.14g of concentrated sulfuric acid as a dehydrating agent to dehydrate and obtain a mixed solution; weigh 1.0g of SBA-15 and pour it into a beaker, then slowly drop 5.0mL of the above mixed solution into the beaker containing SBA-15, ultrasonically treat it for 10min, place it in a muffle furnace, heat it to 100℃ at a heating rate of 10℃ / min and keep it for 6h, then heat it to 160℃ at a heating rate of 10℃ / min and keep it for 6h to obtain an ordered mesoporous carbon material intermediate.
[0042] The ordered mesoporous carbon intermediate was scraped out from the beaker, poured into an agate mortar and ground for 10 min, and then spread flat in a quartz boat. The quartz boat was placed in a tube furnace, heated to 600 °C at a heating rate of 1 °C / min under a nitrogen atmosphere and calcined for 3 h, then heated to 1000 °C at a heating rate of 5 °C / min and calcined for 2 h. The obtained black solid product was placed in 50 mL of 2.0 mol·L -1 The mixture was stirred in an oil bath at 80 °C for 24 h in a sodium hydroxide solution, and the above operation was repeated three times to completely remove the hard template; then the mixture was filtered and washed with a large amount of deionized water until neutral, and the black solid was collected and dried in an oven at 80 °C overnight to obtain an ordered mesoporous carbon material rich in edge defects (OMC-Zn X , X=0.275, 0.55, 1.1).
[0043] 20.0 mg of the obtained ordered mesoporous carbon material rich in edge defects was weighed and dispersed in a round-bottom flask containing 50.0 mL of ethylene glycol, and then 2.5 mL, 2.0 mol·L -1 Chloropalkaline acid solution was stirred for 8 h, 3.0 mL of hydrazine hydrate was added, and stirring was continued for 2 h; then, it was filtered and the surfactant was washed off with a large amount of deionized water; the black solid powder was collected and placed in a vacuum drying oven at 60 ° C overnight to obtain an ordered mesoporous carbon-supported palladium nanoparticle catalyst rich in edge defects (Pd / OMC-Zn X , X=0.275, 0.55, 1.1).
[0044] Example 2
[0045] Weigh 1.25g of sucrose and 0.48g of urea into a centrifuge tube, then accurately measure 10.0mL of deionized water and add it to the above centrifuge tube, stir until completely dissolved, then add 0.14g of concentrated sulfuric acid as a dehydrating agent and stir evenly for dehydration to obtain a mixed solution; weigh 1.0g of SBA-15 and pour it into a beaker, then take 5.0mL of the mixed solution and slowly drop it into the beaker containing SBA-15, ultrasonically treat it for 10min, place it in a muffle furnace, heat it to 100℃ at a heating rate of 3℃ / min and keep it for 6h, then heat it to 160℃ at a heating rate of 20℃ / min and keep it for 6h to obtain an ordered mesoporous carbon material intermediate.
[0046] The ordered mesoporous carbon intermediate was scraped out of the beaker, poured into an agate mortar and ground for 30 min, and then spread flat in a quartz boat. The quartz boat was placed in a tube furnace and heated to 600 °C at a heating rate of 3 °C / min for 3 h under a nitrogen atmosphere, and then heated to 1150 °C at a heating rate of 10 °C / min for 2 h. The obtained black solid product was placed in 50 mL of 2 mol·L -1 The mixture was stirred in a sodium hydroxide solution at 80 °C oil bath for 24 h, and the above operation was repeated three times to completely remove the hard template; then it was filtered and washed with a large amount of deionized water until neutral, the black solid was collected and dried in an oven at 80 °C overnight to obtain an ordered mesoporous carbon material rich in topological defects (OMC-N).
[0047] Weigh 20.0 mg of the obtained ordered mesoporous carbon material rich in topological defects and disperse it in a round-bottom flask containing 50.0 mL of ethylene glycol. Then add 2.5 mL of 2 mol·L -1 Chloropalkaline acid solution was stirred for 8 h, 3.0 mL of hydrazine hydrate was added, and stirring was continued for 2 h; then, it was filtered and the surfactant substances were washed off with a large amount of deionized water; the black solid powder was collected, placed in a vacuum drying oven, and dried at 60 ° C overnight to obtain a topological defect-rich ordered mesoporous carbon-supported palladium nanoparticle catalyst (Pd / OMC-N).
[0048] Example 3
[0049] Weigh 1.25g of sucrose and 0.55g of potassium hydroxide and place them in a centrifuge tube, then accurately measure 10.0mL of deionized water and add it to the above centrifuge tube, stir to form a uniform solution; then add 0.14g of concentrated sulfuric acid as a dehydrating agent to dehydrate, and obtain a dehydrated precursor solution; weigh 1.0g of SBA-15 and pour it into a beaker, take 5.0mL of the above dehydrated precursor solution and slowly drop it into the beaker containing SBA-15, then ultrasonically treat it for 10 minutes to improve its dispersibility, and then place it in a muffle furnace, heat it to 100℃ at a heating rate of 10℃ / min and keep it for 6h, and then heat it to 160℃ at a heating rate of 10℃ / min and keep it for 6h to obtain an ordered mesoporous carbon material intermediate.
[0050] The ordered mesoporous carbon intermediate was scraped out from the beaker, poured into an agate mortar and ground for 10 min, and then spread in a quartz boat; the quartz boat was placed in a tube furnace, and in a nitrogen atmosphere, the temperature was first raised to 600°C at a rate of 1°C / min and calcined for 3 h, and then raised to 1000°C at a rate of 5°C / min and calcined for 2 h. The obtained black solid product was placed in 50 mL of 2.0 mol·L -1 In sodium hydroxide solution, stir in an 80°C oil bath for 24 hours, and repeat the above operation three times to completely remove the hard template; then use a large amount of deionized water to wash until neutral, collect the black solid and dry it in an oven at 80°C overnight to obtain an ordered mesoporous carbon material rich in edge defects.
[0051] 20.0 mg of the obtained ordered mesoporous carbon material rich in edge defects was weighed and dispersed in a round-bottom flask containing 50.0 mL of ethylene glycol, and then 2.5 mL, 2.0 mol·L -1 Chloropalkaline acid solution was stirred for 8 h, 3.0 mL of hydrazine hydrate was added, and stirring was continued for 2 h; the surfactant substance was then washed away with a large amount of deionized water; the black solid powder was collected, placed in a vacuum drying oven, and dried at 60 ° C overnight to obtain an ordered mesoporous carbon-supported palladium nanoparticle catalyst rich in edge defects.
[0052] Example 4
[0053] Weigh 1.25g of sucrose and 0.24g of melamine and place them in a centrifuge tube, then accurately measure 10.0mL of deionized water and add it to the above centrifuge tube, stir until completely dissolved, then add 0.14g of concentrated sulfuric acid as a dehydrating agent and stir evenly for dehydration to obtain a dehydrated precursor solution; weigh 1.0g of SBA-15 and pour it into a beaker, then take 5.0mL of the above dehydrated precursor solution and slowly drop it into the beaker containing SBA-15, then ultrasonically treat it for 10 minutes to improve its dispersibility, place it in a muffle furnace, heat it to 100°C at a heating rate of 10°C / min and keep it for 6h, and then heat it to 160°C at a heating rate of 10°C / min and keep it for 6h to obtain an ordered mesoporous carbon material intermediate.
[0054] The ordered mesoporous carbon intermediate was scraped out of the beaker, poured into an agate mortar and ground for 30 min, and then spread flat in a quartz boat. The quartz boat was placed in a tube furnace and heated to 600 °C at a heating rate of 1 °C / min for 3 h under a nitrogen atmosphere, and then heated to 1150 °C at a heating rate of 5 °C / min for 2 h. The obtained black solid product was placed in 50 mL of 2 mol·L -1In sodium hydroxide solution, stir in an oil bath at 80°C for 24 hours, and repeat the above operation three times to completely remove the hard template; then filter and wash with a large amount of deionized water until neutral, collect the black solid and dry it in an oven at 80°C overnight to obtain an ordered mesoporous carbon material rich in topological defects.
[0055] Weigh 20.0 mg of the obtained ordered mesoporous carbon material rich in topological defects and disperse it in a round-bottom flask containing 50.0 mL of ethylene glycol. Then add 2.5 mL of 2 mol·L -1 Chloropalkaline acid solution was stirred for 8 h, 3.0 mL of hydrazine hydrate was added, and stirring was continued for 2 h; then, it was filtered and the surfactant substances were washed off with a large amount of deionized water; the black solid powder was collected, placed in a vacuum drying oven, and dried at 60 ° C overnight to obtain an ordered mesoporous carbon-supported palladium nanoparticle catalyst rich in topological defects.
[0056] Example 5
[0057] Weigh 1.25g of sucrose, 0.36g of urea, and 0.275g of ZnO quantum dots and place them in a centrifuge tube. Then accurately measure 10.0mL of deionized water and add it to the above centrifuge tube. After stirring until completely dissolved, add 0.14g of concentrated sulfuric acid as a dehydrating agent and stir evenly for dehydration to obtain a dehydrated precursor solution; weigh 1.0g of SBA-15 and pour it into a beaker. Then take 5.0mL of the above dehydrated precursor solution and slowly drop it into the beaker containing SBA-15, then ultrasonically treat it for 10 minutes to improve its dispersibility, place it in a muffle furnace, heat it to 100°C at a heating rate of 2°C / min and keep it for 6h, and then heat it to 160°C at a heating rate of 15°C / min and keep it for 6h to obtain an ordered mesoporous carbon material intermediate.
[0058] The ordered mesoporous carbon intermediate was scraped out from the beaker, poured into an agate mortar and ground for 30 min, and then spread flat in a quartz boat. The quartz boat was placed in a tube furnace and heated to 600 °C at a heating rate of 2 °C / min for 3 h under a nitrogen atmosphere, and then heated to 1150 °C at a heating rate of 10 °C / min for 2 h. The obtained black solid product was placed in 50 mL of 2 mol·L -1 In sodium hydroxide solution, stir in an 80°C oil bath for 24 hours, repeat the above operation three times to completely remove the hard template; then filter and wash with a large amount of deionized water until neutral, collect the black solid and dry it in an oven at 80°C overnight to obtain an ordered mesoporous carbon material rich in intrinsic defects.
[0059] 20.0 mg of the ordered mesoporous carbon material rich in edge defects and topological defects was weighed and dispersed in a round-bottom flask containing 50.0 mL of ethylene glycol. Then 2.5 mL of 2 mol·L -1Chloropalkaline acid solution was stirred for 8 h, 3.0 mL of hydrazine hydrate was added, and stirring was continued for 2 h; then, it was filtered and the surfactant substances were washed off with a large amount of deionized water; the black solid powder was collected, placed in a vacuum drying oven, and dried at 60 ° C overnight to obtain an ordered mesoporous carbon-supported palladium nanoparticle catalyst rich in topological defects.
[0060] Comparative Example 1
[0061] Weigh 1.25g of sucrose and place it in a centrifuge tube, then accurately measure 10.0mL of deionized water and add it to the above centrifuge tube, stir until it is completely dissolved, then add 0.14g of concentrated sulfuric acid as a dehydrating agent for dehydration and stir evenly to obtain a dehydrated precursor solution; weigh 1.0g of SBA-15 and pour it into a beaker, then take 5.0mL of the dehydrated precursor solution and slowly drop it into the beaker containing SBA-15, then ultrasonically treat it for 10 minutes to improve its dispersibility, place it in a muffle furnace, heat it to 100°C at a heating rate of 10°C / min and keep it for 6h, then heat it to 160°C at a heating rate of 10°C / min and keep it for 6h, to obtain a composite of ordered mesoporous carbon and SBA-15.
[0062] 20.0 mg of the obtained complex was weighed and dispersed in a round-bottom flask containing 50.0 mL of ethylene glycol, and then 2.5 mL of 2 mol·L -1 The chloropalladic acid solution was stirred for 8 h, 3.0 mL of hydrazine hydrate was added, and stirring was continued for 2 h; then, it was filtered, and the surfactant substances were washed off with a large amount of deionized water. The black solid powder was collected, placed in a vacuum drying oven, and dried at 60°C overnight to obtain the ordered mesoporous carbon-supported palladium nanoparticle catalyst (Pd / OMC-1000) of this comparative example.
[0063] Comparative Example 2
[0064] Weigh 1.25g of sucrose and place it in a centrifuge tube, then accurately measure 10.0mL of deionized water and add it to the above centrifuge tube, stir until it is completely dissolved, then add 0.14g of concentrated sulfuric acid as a dehydrating agent for dehydration and stir evenly to obtain a dehydrated precursor solution; weigh 1.0g of SBA-15 and pour it into a beaker, then take 5.0mL of the dehydrated precursor solution and slowly drop it into the beaker containing SBA-15, then ultrasonically treat it for 10 minutes to improve its dispersibility, place it in a muffle furnace, heat it to 100°C at a heating rate of 10°C / min and keep it for 6h, then heat it to 160°C at a heating rate of 10°C / min and keep it for 6h, to obtain a composite of ordered mesoporous carbon and SBA-15.
[0065] The above-mentioned composite was scraped out from the beaker, poured into an agate mortar and ground for 30 minutes, and then spread flat in a quartz boat; the quartz boat was placed in a tube furnace, heated to 600°C at a heating rate of 1°C / min under a nitrogen atmosphere and calcined for 3 hours, and then heated to 1150°C at a heating rate of 5°C / min and calcined for 2 hours; the obtained black solid product was placed in 50 mL of 2 mol·L -1 In sodium hydroxide solution, stir in an 80°C oil bath for 24 hours, repeat the above operation three times to completely remove the hard template; then filter and wash with a large amount of deionized water until neutral, collect the black solid and dry it in an oven at 80°C overnight to obtain the ordered mesoporous carbon material of this comparative example.
[0066] Weigh 20.0 mg of the obtained ordered mesoporous carbon material and disperse it in a round-bottom flask containing 50.0 mL of ethylene glycol, then add 2.5 mL of 2 mol·L -1 The chloropalladium acid solution was stirred for 8 hours, 3.0 mL of hydrazine hydrate was added, and stirring was continued for 2 hours; then, it was filtered, and the surfactant substances were washed off with a large amount of deionized water. The black solid powder was collected, placed in a vacuum drying oven, and dried at 60°C overnight to obtain the ordered mesoporous carbon-supported palladium nanoparticle catalyst of this comparative example.
[0067] Experimental example
[0068] (1) Electrochemical testing method
[0069] 2.0 mg of the catalysts of Example 1-2 and Comparative Example 1-2 were dispersed in a centrifuge tube containing 450 μL of anhydrous ethanol, 500 μL of deionized water, and 50 μL of Nafion membrane solution to prepare a catalyst slurry. 5 μL was taken each time for electrochemical testing. The electrochemical test was carried out in a three-electrode system with a saturated calomel electrode as the counter electrode, a glassy carbon electrode as the working electrode, and a platinum electrode as the counter electrode. The electrolyte was 1.0 mol·L -1 Potassium hydroxide plus methanol solution or 1.0 mol·L -1 Potassium hydroxide solution.
[0070] (2) Characterization and test results
[0071] Figure 1 Figures are scanning electron microscope (SEM) images of the catalysts prepared in Example 1 and Comparative Example 1, wherein a and b are scanning electron microscope images of the catalyst prepared in Comparative Example 1, and c and d are scanning electron microscope images of the catalyst prepared in Example 1 when the addition amount of ZnCl2 is 0.55 g. Figure 1 As shown, the surface of the unmodified ordered mesoporous carbon carrier in Comparative Example 1 is smooth, while the surface of the modified defect-rich ordered mesoporous carbon carrier in Example 1 has more wrinkles, indicating that more edge defects are exposed on the surface of the modified ordered carbon carrier.
[0072] Figure 2 The X-ray diffraction (XRD) patterns of the defect-rich ordered mesoporous carbon-supported palladium nanoparticle catalysts prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 2 As shown, the catalysts prepared in Example 1 and Comparative Example 1 show the diffraction peaks of Pd, proving that the Pd nanoparticles are successfully loaded on the defect-rich ordered mesoporous carbon support. In addition, it can be clearly seen that the diffraction peak intensity of Pd in the catalyst prepared in Example 1 is significantly lower than that in Comparative Example 1, which indicates that the edge defect-rich ordered mesoporous carbon promotes the dispersion of Pd nanoparticles.
[0073] Figure 3 Figures 1 and 2 are nitrogen adsorption isotherms of the catalysts prepared in Example 1 and Comparative Example 1. a is the nitrogen adsorption isotherm of the catalyst prepared in Example 1, and b is the nitrogen adsorption isotherm of the catalyst prepared in Comparative Example 1. Figure 3 It can be seen that the catalysts prepared in Example 1 and Comparative Example 1 both exhibit type IV isotherms, indicating that they retain their mesoporous structures.
[0074] Figure 4 The Raman spectra of the catalysts prepared in Example 1 and Comparative Example 1 are shown in Figure 1, where a is the Raman spectra of the catalyst prepared in Comparative Example 1, and bd is the Raman spectra of the catalyst prepared in Example 1. The obtained spectra were subjected to peak fitting and deconvoluted into four carbon configurations, namely, the G band (1580cm-1) associated with the graphite domain, -1 ), the D1 band (1340 cm -1 )、D2 belt (1200cm -1 )、D3 belt (1500cm -1 ), wherein the D1 band is related to the edge defects of the carbon carrier, therefore, the edge defect density of the modified ordered mesoporous carbon in Example 1 is significantly improved.
[0075] Figure 5 The chronoamperometry (CA) curves of the catalysts prepared in Example 1 and Comparative Example 1 in the methanol electrocatalytic oxidation reaction show that when the addition amount of ZnCl2 is 0.55 g, the stability of the catalyst is improved, and the activity is 700 mA mg after constant potential discharge at -0.2 V for 200 s. -1 Pd .
[0076] Figure 6The cyclic voltammetry curves (CV) of the catalysts prepared in Example 1 and Comparative Example 1 in the methanol electrocatalytic oxidation reaction show that the mass specific activity of the catalyst in Example 1 is significantly improved, especially when the addition amount of ZnCl2 is 0.55g, its activity is twice that of the catalyst in the comparative example.
[0077] Figure 7 The X-ray photoelectron spectroscopy (XPS) of the catalysts prepared in Example 1 and Comparative Example 1; Figure 7 As shown, compared with the unmodified ordered mesoporous carbon in Comparative Example 1, the binding energy of the metal Pd species in the catalyst of Example 1 is positively shifted by 0.03 eV, 0.44 eV, and 0.02 eV, respectively. This shift indicates the electron-deficient characteristics of the Pd nanoparticles, which means that after the introduction of the mesoporous structure, electrons are transferred from the Pd nanoparticles to the carbon support; this indicates that the edge defects exposed in the mesoporous structure may enhance the Electronic Metal-Support Interaction (EMSI) and promote the transfer of electrons from the palladium nanoparticles to the carbon support.
[0078] Table 1 shows the metal loadings obtained by inductively coupled plasma atomic emission spectrometry (ICP-OES) of the catalysts prepared in Example 1 and Comparative Example 1; it can be seen that, under the premise of consistent theoretical loadings, the loading of Pd nanoparticles in the defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst prepared by the method of the present invention is significantly increased. Crucially, only a small amount of Zn atoms were monitored, which eliminates the influence of heteroatoms on the electrocatalytic oxidation performance of methanol.
[0079] Table 1
[0080] catalyst Pd loading (wt%) Zn loading (wt%) <![CDATA[Pd / OMC-Zn 0.275 ]]> 13.3 0.01 <![CDATA[Pd / OMC-Zn 0.55 ]]> 32.2 0.05 <![CDATA[Pd / OMC-Zn 1.1 ]]> 23.8 0.03 Pd / OMC-1000 10.9 -
[0081] Table 2 shows the numerical values of the pore structures of the supports prepared in Example 1 and Comparative Example 1. It can be seen that the specific surface area, pore volume and pore volume of the supports before and after modification remain basically unchanged, which plays a crucial role in studying the effect of inherent defects on the electrocatalytic oxidation performance of methanol.
[0082] Table 2
[0083] Carrier <![CDATA[Specific surface area (m 2 / g)]]> Pore size (nm) <![CDATA[Pore volume (m 3 ·g -1 )]]> OMC-1000 1356 4.92 0.38 OMC-Zn0.275 1274 7.10 0.37 OMC-Zn0.55 1250 9.08 0.37 OMC-Zn1.1 1308 8.47 0.40
[0084] Figure 8The XPS spectra of the catalysts prepared in Example 2 and Comparative Example 2 are as follows; it can be seen that the carbon support with topological defects can also enhance the EMSI between the support and the metal, and promote the degree of electron transfer between the Pd nanoparticles and the carbon support.
[0085] Fig. 9 CV curves of the catalysts prepared in Example 2 and Comparative Example 2; it can be seen that the Pd nanoparticle catalyst supported by the carbon carrier with topological defects can significantly improve its methanol electrocatalytic oxidation activity.
[0086] Combination Figures 1 to 7 It can be seen that the pore size of the defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst prepared by the method of the present invention is 2 to 8 nm, and the degree of edge defects is significantly improved; the activity of the palladium nanoparticle catalyst supported by it in the methanol electrocatalytic oxidation reaction is 5027 mA·mg -1 The Pd is twice that of the control, and the stability is also improved. This is because the edge defects of the carbon carrier significantly enhance the EMSI between the metal and the carrier, and the electrons are transferred from the metal to the carrier, which reduces the electron cloud density of the Pd nanoparticles (NPs), thereby improving the catalytic activity.
[0087] Combination Figure 8-9 It can be seen that the topological defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst prepared by the method of the present invention has a good effect on enhancing the EMSI between the metal and the carrier and improving the activity of the methanol electrocatalytic oxidation reaction.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the technical solution and conceptual invention of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst, characterized in that: include: (1) Dissolving 1 to 3 parts of a carbon source and 0.2 to 1.5 parts of a defect-causing agent in an appropriate amount of deionized water by weight to obtain a precursor solution; then adding 0.05 to 0.15 parts of concentrated sulfuric acid for dehydration, and then dispersing the mixed solution into 1 part of a hard template by ultrasonication, and then drying by gradient heating to obtain an ordered mesoporous carbon material intermediate; the carbon source is sucrose, and the hard template is SBA-15; (2) taking one portion of the ordered mesoporous carbon material intermediate, subjecting it to high temperature heat treatment in an inert atmosphere, then removing the hard template with a strong alkaline solution, then washing the product with water until it is neutral, and drying it, and the obtained solid product is defect-rich ordered mesoporous carbon; (3) The defect-rich ordered mesoporous carbon obtained in step (2) is subjected to impregnation and chemical reduction steps with a metal precursor solution to obtain a defect-rich ordered mesoporous carbon-loaded metal nanoparticle catalyst.
2. The method for preparing a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst according to claim 1, characterized in that: In step (1), the defect-causing agent is at least one of zinc chloride, zinc oxide quantum dots, potassium hydroxide, urea, and melamine.
3. The method for preparing a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst according to claim 1, characterized in that: In step (1), the dehydrated precursor solution is added to the hard template twice, and gradient drying is performed each time; the gradient drying is performed in a muffle furnace, firstly heating to 100°C at a heating rate of 1 to 3°C / min, maintaining for 6 hours, then heating to 160°C at a heating rate of 10 to 20°C / min, and maintaining for another 6 hours.
4. The method for preparing a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst according to claim 1, characterized in that: In step (2), the high temperature heat treatment under an inert atmosphere is carried out in two stages. First, the temperature is raised to 600°C for pre-carbonization at a heating rate of 1 to 3°C / min for 3 hours, and then the temperature is raised to 1000 to 1200°C for carbonization at a heating rate of 5 to 10°C / min for 2 hours.
5. The method for preparing a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst according to claim 1, characterized in that: In step (2), the specific process of removing the hard template with a strong alkali solution is as follows: the solid product after high-temperature heat treatment under an inert atmosphere is added to a strong alkali solution, stirred for 24 hours in an oil bath at 60 to 100° C., and the operation is repeated three times; the strong alkali solution is an aqueous solution of sodium hydroxide or potassium hydroxide with a mass percentage of 8 to 12%.
6. The method for preparing a defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst according to claim 1, characterized in that: In step (3), the metal precursor used in the metal precursor solution is a metal precursor containing any one of Pt, Pd, Ru, Rh, Ir, Fe, Co, Ni, Cu, and Zn.
7. A defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst, prepared by the preparation method of the defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst according to any one of claims 1 to 6; the defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst has a pore size of 2 to 10 nm and a mass specific activity of 4000 to 5027 mA·mg -1 metal .
8. Use of the defect-rich ordered mesoporous carbon-supported metal nanoparticle catalyst according to claim 7 in the electrocatalytic oxidation reaction of methanol at the anode of a direct methanol fuel cell.